Feasibility of a mass vaccination campaign using a two-dose oral cholera vaccine in an urban cholera-endemic setting in Mozambique. - Cavailler, P; Lucas, M; Perroud, V; McChesney, M; Ampuero, S; Guérin, P; Legros, D; Nierle, T; Mahoudeau, C; Lab, B; Kahozi, P; Deen, J; et al. (2006)
We conducted a study to assess the feasibility and the potential vaccine coverage of a mass vaccination campaign using a two-dose oral cholera vaccine in an urban endemic neighbourhood of Beira, Mozambique. The campaign was conducted from December 2003 to January 2004. Overall 98,152 doses were administered, and vaccine coverage of the target population was 58.6% and 53.6% for the first and second rounds, respectively. The direct cost of the campaign, which excludes the price of the vaccine, amounted to slightly over 90,000 dollars, resulting in the cost per fully vaccinated person of 2.09 dollars, which is relatively high. However, in endemic settings where outbreaks are likely to occur, integrating cholera vaccination into the routine activities of the public health system could reduce such costs.